PERAN FLASH SALES, HARGA DAN TRUST DALAM MEMBENTUK KEPUTUSAN PEMBELIAN ONLINE: STUDI PADA PENGGUNA APLIKASI SHOPEE - Ferry Adi Wibowo; Heni Susilowati (ITB AAS Indonesia Surakarta, 2026)
The digital era is driving rapid growth in the communications and information sector, including the rise of e-commerce in Indonesia. Digital transformation is changing people's lifestyles, including online shopping activities. Shopee, as one of the leading e-commerce platforms, was chosen as the object of research, aiming to analyze the influence of flash sales, prices, and trust on online purchasing decisions. This study uses a quantitative descriptive approach, involving 100 active Shopee users as respondents using a non-probability sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study prove that trust has the most dominant impact on online purchasing decisions, followed by flash sales and prices. Simultaneously, all three variables of flash sales, price, and trust contribute significantly to online purchasing decisions. The implications of the research are that Shopee continues to increase the frequency and transparency of flash sales, offer more competitive prices, and provide fast and responsive service to build customer trust and loyalty. Keywords : Flash sales;Price;Trust;Purchase Decisions